Promotion of health-enhancing physical activity in the sport sector: a study among representatives of 536 sports organisations from 36 European countries - Tena Matolić; Danijel Jurakić; Hrvoje Podnar; Ivan Radman; Željko Pedišić (BMC, 2023)
Abstract Background It is a common belief that most sports clubs and organisations are primarily focused on elite sports while placing less emphasis on the promotion of health-enhancing physical activity (HEPA). However, there is a lack of evidence on this topic in the scientific literature. Therefore, the aim of this study was to determine the level and correlates of the commitment of sports organisations in Europe to HEPA promotion. Methods Representatives of 536 sports organisations from 36 European countries responded to our survey. A multiple regression analysis was conducted with the commitment of sports organisation to HEPA promotion (0 ["not at all"] - 10 ["most highly"]) as the outcome variable and organisation type ("national sport association" reference group [ref], "European sports federation", "national umbrella sports organisation", "national Olympic committee", "national sport-for-all organisation"), headquarters in a European Union member state ("no" [ref], "yes"), region of Europe ("Western" [ref], "Central and Eastern", "Northern", "Southern"), commitment to elite sports ("low" [ref], "medium", "high"), and awareness of Sports Club for Health (SCforH) guidelines ("no" [ref], "yes") as explanatory variables. Results Approximately 75.2% (95% confidence interval [CI]: 71.5, 78.8) of sports organisations were highly committed to elite sports. Only 28.2% (95% CI: 24.4, 32.0) of sports organisations reported a high commitment to HEPA promotion. A higher commitment to HEPA promotion was associated with the national Olympic committees (β = 1.48 [95% CI: 0.41, 2.55], p = 0.007), national sport-for-all organisations (β = 1.68 [95% CI: 0.74, 2.62], p < 0.001), location in Central and Eastern Europe (β = 0.56 [95% CI: 0.01, 1.12], p = 0.047), and awareness of SCforH guidelines (β = 0.86 [95% CI: 0.35, 1.37], p < 0.001). Conclusion From our findings, it seems that most sports organisations are primarily focused on elite sports. Coordinated actions at the European Union and national levels are needed to improve the promotion of HEPA through sports organisations. In this endeavour, it may be useful to consider national Olympic committees, national sport-for-all organisations, and relevant sports organisations in Central and Eastern Europe as role models and to raise the awareness of SCforH guidelines.